2012
DOI: 10.1080/19361521.2012.671796
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing PTSD: Traumatic Experiences, Posttraumatic Symptom Clusters, and Mental Health Problems among Delinquent Youth

Abstract: This study investigated interrelations among trauma exposure, posttraumatic stress disorder (PTSD) symptom clusters, and mental health problems among adjudicated adolescents. Girls scored higher than boys on measures of exposure to interpersonal trauma, PTSD symptom clusters, and mental health problems. Results of path analyses were consistent with the hypothesis that PTSD symptom clusters differentially mediate the relations between trauma exposure and mental health problems, with unique patterns of results f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
40
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 33 publications
6
40
1
Order By: Relevance
“…With respect to gender differences, Kerig, Vanderzee, Becker, and Ward (2012) found that females endorsed experiencing more interpersonal trauma, greater PTSD symptoms, and more mental health problems as compared to males. For all youth, avoidance mediated the relationship between trauma and internalizing symptoms, while re-experiencing and arousal mediated externalizing symptoms.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…With respect to gender differences, Kerig, Vanderzee, Becker, and Ward (2012) found that females endorsed experiencing more interpersonal trauma, greater PTSD symptoms, and more mental health problems as compared to males. For all youth, avoidance mediated the relationship between trauma and internalizing symptoms, while re-experiencing and arousal mediated externalizing symptoms.…”
mentioning
confidence: 95%
“…For males specifically, noninterpersonal traumas were associated with PTSD symptoms, which mediated internalizing symptoms. For females only, re-experiencing and arousal mediated internalizing symptoms, and related PTSD symptoms mediated externalizing symptoms (Kerig, Vanderzee, et al, 2012). Physical abuse, sexual abuse, and witnessing violence have been found to predict delinquency among males, while sexual abuse predicts delinquency for females (Begle et al, 2011).…”
mentioning
confidence: 95%
“…These rates of traumatization are notable in comparison to estimates that about 36% of individuals in the general population (e.g., Dorrington et al, 2014) and 92% in high-risk areas (e.g., Detroit, Michigan; Breslau, 2009) have experienced at least one PTE. Given the robust links between trauma experience and delinquent recidivism (e.g., Kerig, Vanderzee, Becker, & Ward, 2012), the alarmingly high rates found in our sample must be considered across the mental health research, intervention, and policy spheres to promote adaptive functioning for incarcerated women. Furthermore, being arrested and experiences while incarcerated may perpetuate the trauma–recidivism cycle, as both experiences have demonstrated the function of further traumatization in prior studies (e.g., Wolf, Silva, Knight, & Javdani, 2007), particularly for women (Moloney, Van Den Bergh, & Moller, 2009).…”
Section: Discussionmentioning
confidence: 95%
“…Also, adolescent female offenders more often have developed mental health problems, internalizing problems and disorders in particular, such as depression, anxiety, and PTSD than their male counterparts (e.g., Adams et al, 2013;Cauffman et al, 2007;Chitsabesan et al, 2006;Van Damme et al, 2016;Wasserman et al, 2005). Gender differences in PTSD in particular are large (Kerig, Vanderzee, Becker, & Ward, 2012). For example, PTSD is more common among incarcerated adolescent females (23-45%) than among adolescent males (9-26%; Abram et al, 2004, Adams et al, 2013Kerig et al, 2009;Robertson, Dill, Husain, & Undesser, 2004;Steiner, Garcia, & Matthews, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Internalizing mental health problems were defined as having solely internalizing symptoms or being diagnosed with an internalizing disorder (mood or anxiety disorder, including PTSD). We made this distinction in solely having symptoms and being diagnosed with a disorder because although internalizing symptoms are regularly seen in both delinquent males and females, females are more often diagnosed with severe internalizing disorders (see Kerig et al, 2012). We expect the difference in mental health problems between males and females more strongly in internalizing disorders.…”
Section: Introductionmentioning
confidence: 99%